Antithrombotic alternatives for stroke prevention in atrial fibrillation: critical differences and remaining questions - James S Kalus (BioExcel Publishing Ltd, 2013)
Three therapeutic alternatives for prevention of stroke in patients with atrial fibrillation are available in dabigatran (an oral direct thrombin inhibitor), rivaroxaban, and apixaban (both oral blood coagulation factor Xa inhibitors). Compared with warfarin, these new agents have a more predictable pharmacodynamic response and fewer major clinically relevant drug-drug interactions. These agents also have few, if any, food-drug interactions, and infrequent or no need for routine laboratory monitoring. These agents also bring new disadvantages, particularly lack of clearly defined reversal strategies, inability to effectively monitor patient response, and higher cost. Selection of the most appropriate oral antithrombotic agent for a given patient is dependent on clinician knowledge of the similarities and critical differences between the available antithrombotic medications.